Peranan Komite Audit Mengoptimalkan Fungsi Auditor Internal dalam Penerapan Good Corporate Governance di PT BNI.Tbk - Arif Firmansyah (Syiar Hukum, 2010)
Bank is an intermediary between a party who have surplus of funds and those who have lack of fund. In this respect,  public trust depends on bank work performance and its ability to manage risk, professionalism and integrity of the bank board and public transparency.  This article discusses the role of Audit Committee to optimize the internal auditor function in the implementation of good corporate governance in BNI 1946 Limited Company.   The article examines   some challenges of the Audit Committee in optimizing such function.  These include the Audit Committee’s inability to (1) boost the Bank Commissioner  in doing supervision and (2) assist Supervision Internal Unit in obtaining accurate data. The author recommends  that accountability and commitment of company board should be conducted professionally in order to effectively optimize the  role of Audit Committee.